Sustainable coasts? Perceptions of change and livelihood vulnerability in Nordland, Norway - Rybråten, Stine; Bjørkan, Maiken; Hovelsrud, Grete K.; Kaltenborn, Bjørn Petter (Local Environment, 2018)
Author's accepted version (post-print). Available from 17/10/2019. Northern coastal regions are facing multiple challenges from accelerating global environmental and socioeconomic changes, such as ecosystem degradation, climate change, intensified resource extraction, land use change and declining populations. Based on interviews with 13 farmers, fishers and aquaculture employees from coastal Nordland, northern Norway, this study demonstrates how the local stakeholders’ perceptions of change and experiences of vulnerability are closely linked to their livelihood values and worldviews. What the informants consider a sustainable and meaningful way of coastal living does not coincide with national goals for sustainable, natural resource dependent development of the region. The article demonstrates the importance of attending to local values if policymakers and managers are to ensure successful local mobilisation, reduce vulnerability to ongoing and future processes of change, and ensure legitimacy and consistency in development goals of coastal zone management. Insights from this study are useful for local and regional decision makers with responsibility for natural resource policies and development efforts. Perceptions of change, livelihood values, worldviews, sustainability, coastal regions, Northern Norway. acceptedVersion